Handsigns - Fain, Kathleen (San Francisco : Chronicle Books, 1993)
Presents an animal for each letter of the alphabet, accompanied by the corresponding sign for that letter in American Sign Language.
Keywords: American Sign Language -- Alphabet -- Juvenile literature; Sign language; Alphabet; Animals